Intrahousehold Allocation and Gender Relations: New Empirical Evidence from Four Developing Countries - Quisumbing, Agnes R.; Maluccio, John A. (International Food Policy Research Institute, 2003)
Most economic research treats the household as a single agent, assuming that individuals within the household share the same preferences or that there is a household “head” who has the final say. This simple framework has proved immensely useful; despite a common misperception, it can explain many differences in well-being or consumption patterns within households. Nonetheless, recent empirical research demonstrates that this “unitary” household model is inappropriate in a variety of settings in both developed and developing countries (see Haddad, Hoddinott, and Alderman 1997 for reviews).